Nitrogen-Doped Carbon Nanosheets Decorated With Mn2O3 Nanoparticles for Excellent Oxygen Reduction Reaction - Qasim, Maryam; Hou, Jianhua; Qadeer, M. A.; Butt, Sajid; Farooq, M. Hassan; Farooq, M. Qasim; Idrees, Faryal; Tanveer, M.; Zou, Jijun; Tahir, Muhammad (Frontiers in Chemistry, 2019)
The purpose of this study is to develop an active, low cost, non-precious, stable and high performance catalyst for oxygen reduction reaction (ORR). In this regard, Mn2O3 decorated nitrogen-doped carbon (Mn2O3/NC) nanosheets is fabricated by two-step strategy, involving hydrothermal method and solid-state method. The resultant structures have very fine Mn2O3 nanoparticles with average size of about 5nm, strongly attached with nitrogen doped carbon nanosheets. The role of Mn2O3 nanoparticles is to provide active sites for ORR while the presence of nitrogen doped carbon not only enhanced the conductivity of the overall structures but also helpful for overall stability. The Mn2O3/NC shows good onset potential (0.80V@-1mA/cm2), methanol cross over effect and stability (90%).